2020
DOI: 10.1007/s11250-020-02416-1
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive survey of porcine epidemic diarrhea in pig populations in northern Vietnam

Abstract: Porcine epidemic diarrhea (PED) virus (PEDV) is a globally emerging and re-emerging epizootic swine virus that causes massive economic losses in the swine industry, with high mortality in piglets. In Vietnam, PED first emerged in 2009 and has now developed to an endemic stage. This is the first cross-sectional survey performed to evaluate the proportion of PEDV-positive swine farms in Vietnam from January 2018 to February 2019. Fecal samples from 327 pig farms in northern Vietnam were collected and tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These data again indicated that PEDV infection was naturally widespread in the pig populations in these 3 provinces. In other report, 30.89 % of pig farms were found as PED positive in northern Vietnam which was detected by LAMP method and these farms at northern Vietnam may be the source of transmission in countrywide [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data again indicated that PEDV infection was naturally widespread in the pig populations in these 3 provinces. In other report, 30.89 % of pig farms were found as PED positive in northern Vietnam which was detected by LAMP method and these farms at northern Vietnam may be the source of transmission in countrywide [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…PEDV infection can also cause subclinical infections with no clinical signs in finishing pigs, and these asymptomatic pigs could therefore represent an important risk factor for spreading the disease [ 23 ]. It was reported that 70 % of PED positive farms were subclinically infected in Northern Vietnam and this may be the risk of cross-contamination in pigs in Vietnam [ 21 ]. In the present study, symptoms such as diarrhoea were not observed at most of the pig farms.…”
Section: Discussionmentioning
confidence: 99%
“…The other three farms are located in Ninh Binh and Ha Nam provinces. All provinces in this study are located in northern Vietnam, where the largest populations of pigs are found [26].…”
Section: Data Collectionmentioning
confidence: 99%
“…PEDV was detected in Vietnam in 2008 and rapidly spread throughout the country, causing severe economic loss [ 25 ]. It is now persistent and circulating in the swine populations [ 26 , 27 ]. Studies on the S gene sequences of PEDV strains isolated during 2012–2016 showed that these strains had undergone substantial changes [ 11 , 28 , 29 ], which might explain the decrease in vaccine efficiency.…”
mentioning
confidence: 99%
“…Studies on the S gene sequences of PEDV strains isolated during 2012–2016 showed that these strains had undergone substantial changes [ 11 , 28 , 29 ], which might explain the decrease in vaccine efficiency. Moreover, PEDV continues to predominate in pig populations, even in vaccinated herds, and has become a persistent endemic nationwide [ 26 , 27 ]. In Vietnam, imported attenuated PEDV and locally produced inactivated vaccines have been used to immunize pigs and sows.…”
mentioning
confidence: 99%